An Introduction to Resource Development in Leisure Education - Ziqi Gong (Journal of Advanced Research in Education, 2024)
“Leisure” refers to the time that the people can really freely dispose of in modern society; leisure education is the education that instructs people how to actively utilize leisure; the resources of leisure education mainly include natural resources and social resources. Reasonable development and utilization of these resources is not only to meet the needs of “leisure” people, but also the needs of leisure education.